PENGARUH MEDIA ULAR TANGGA TERHADAP MINAT BELAJAR MATEMATIKA PESERTA DIDIK PADA MI AL-FITRAH UMI KOTA MAKASSAR - Rayhinnur; Wahab, Abdul; Aidil Sudarmono R, Muh.; Syahid, Akhmad; Martini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine students' perceptions of the Snakes and Ladders learning media, their interest in learning mathematics, and the significant influence between the Snakes and Ladders learning media and their interest in learning mathematics. This study used a quantitative method with a correlation approach, using descriptive statistical analysis and simple linear regression tests. Data collection techniques included observation, documentation, and questionnaires. The sample size was 29 respondents. The results showed: (1) students' perceptions of the Snakes and Ladders learning media were in the good category (77.75%), (2) students' interest in learning mathematics was in the very good category (81.28%), and (3) there was a significant influence between the Snakes and Ladders learning media and their interest in learning mathematics. The hypothesis test showed a significance value (sig.) of 0.003, which is less than 0.05. The correlation determination was 53%, with the remaining 47% influenced by other factors not examined in this study. This indicates that the better the learning through the Snakes and Ladders learning media, the higher the students' interest in learning mathematics. Keywords: Snakes and Ladders Learning Media, Interest in Learning Mathematics, Students